URGENSI PERLINDUNGAN HUKUM TERHADAP JUSTICE COLABORATOR DALAM TINDAK PIDANA KORUPSI: - - Silitonga, Dony Andrianto; Jamba, Padrisan (LPPM Universitas Putera Batam, 2023)
Criminal acts, such as corruption, are illegal actions committed by individuals that harm the state for personalor others' benefits. Corruption is considered an exceptional crime, making investigations challenging due tothe intricate methods employed by the perpetrators. This difficulty led to the introduction of the term